Case Report: CT-guided biopsy of a mediastinal mass in the visceral compartment - Chen, Xiangrui; Hu, Min; Hao, Chengluo; Han, Yunwei; Zhao, Jingting (Frontiers in Oncology, 2026)
BackgroundThe pathological diagnosis of mediastinal lesions is crucial for precision oncology. While endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the preferred minimally invasive method for visceral mediastinal lesions, its diagnostic yield can be limited for high-risk lesions surrounded by great vessels. This case demonstrates that under such complex anatomical constraints, a meticulously planned CT-guided percutaneous biopsy serves as a safe and effective alternative.Case presentationA middle-aged male patient was highly suspected of having lung cancer with mediastinal metastasis based on clinical and radiological findings. Two successive bronchoscopic biopsies of the pulmonary lesion failed to yield a diagnosis. Although the medical team recommended EBUS-TBNA at a tertiary hospital, the patient opted for a CT-guided biopsy at our institution after considering personal convenience and economic factors. The target was a high-risk mediastinal lymph node located within the vascular “core area” between the aorta and superior vena cava.Intervention and outcomePreprocedural planning with contrast-enhanced CT simulated three potential trajectories (transcostochondral, transsternal, transpulmonary). The transsternal approach was prioritized to avoid lung parenchyma, thereby eliminating the risk of pneumothorax—a critical consideration given the patient’s comorbid emphysema and bullae. The initial transcostochondral approach was abandoned due to pain upon vascular contact and restricted maneuverability. The subsequent transsternal approach was successfully performed using a coaxial biopsy system to navigate the narrow vascular space, followed by tract embolization upon needle withdrawal. The procedure was safe, with only minimal, self-resolving mediastinal emphysema. Adequate tissue cores were obtained, enabling a definitive diagnosis of metastatic lung adenocarcinoma.ConclusionFor complex mediastinal lesions where standard approaches are unsuitable or declined by the patient, a meticulously planned CT-guided percutaneous biopsy based on three-dimensional anatomical assessment is a feasible and valuable diagnostic strategy.